Association of prognostic nutritional index with all-cause and cardiovascular mortality in adults with depression: NHANES 2005–2018 - Ding, Haiyan; Zou, Xinchun (Frontiers in Nutrition, 2025)
IntroductionThe Prognostic Nutritional Index (PNI) reflects immune and nutritional status and has been widely used to assess various diseases. However, research on the PNI and mortality in patients with depression is limited.ObjectiveThe study aimed to assess the association between the PNI and both all-cause and cardiovascular disease (CVD) mortality in adults with depression.MethodsThis study analyzed the PNI levels in a cohort of 2,396 adults with depression. The analysis was conducted using data obtained from the National Health and Nutrition Examination Survey (NHANES), which was conducted between 2005 and 2018. Mortality outcomes were determined through a comprehensive review of the National Death Index records through December 31, 2019. Multivariable weighted Cox proportional hazards regression models were employed to investigate the hazard ratios (HRs) and 95% confidence intervals (CIs) for all-cause and CVD mortality. Restricted cubic spline analyses were utilized to explore the potential nonlinear association between PNI levels and mortality.ResultsThe weighted mean PNI level was 41.89 (standard error 0.1), and the median follow-up duration was 84 months. There were 295 all-cause deaths and 73 CVD deaths during the follow-up period. Higher PNI levels were significantly associated with a reduced risk of all-cause mortality (HR, 0.47; 95% confidence interval [CI], 0.31–0.73; p for trend < 0.001) and CVD mortality (HR, 0.51; 95% CI, 0.27–0.96; p for trend = 0.038) compared with lower PNI levels. Each 1-unit increase in PNI was associated with a 12% reduction in the risk of all-cause mortality (HR, 0.88; 95% CI, 0.84–0.93; p < 0.001) and a 12% reduction in the risk of CVD mortality (HR, 0.88; 95% CI, 0.80–0.96; p = 0.006). After multivariable adjustment, a linear association was observed (p for nonlinearity = 0.114 and 0.071 for all-cause and CVD mortality, respectively). Subgroup analyses showed that no statistically significant interactions were observed in any of the subgroups, as the p-values were all above 0.05.ConclusionHigher PNI levels were associated with lower all-cause and CVD mortality in adults with depression. These findings suggest that PNI may serve as a clinically useful indicator to predict the prognosis of patients with depression.